116k views
4 votes
. Evaluate the algebraic expression: a + b + c when a = 2, b = 1, and c = -1

2 Answers

9 votes

Answer:

2

Explanation:

In algebra, you can replace the letters in an equation with whatever number they equal.

So because a = 2, we can replace the a in this formula with the number 2

We can do the same thing for the rest of these letters!

so...

a + b + c

becomes

2 + 1 + (-1)

now all we need to do is solve :)

2 + 1 + (-1)

3 + (-1)

3 - 1

2

User NealeU
by
6.0k points
5 votes
Equals 2 I believe hopefully it helps
2+1+(-1)=2
User Kiuma
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.